A modern comic story: Poverty and distributive justice - GÖK, ALİHAN (My University, 2023)
The understanding of poverty as the main social problem in purely economic terms and the argument that poverty should be eradicated translates to making sense of it as a trans-historical concept entirely independent from capitalism. The modern state considers poverty as a major obstacle to economic development and claims to struggle with it. Social justice has spread to a process of fighting poverty, which becomes a constant pursuit like the struggle and dependence between the hero and antihero common to modern comic books. Far from being identified as an ideal situation that needs to be reached, social justice in the hands of the modern state has transformed into a tool for targeted stability within market conditions. In this process, the recognition involved with identifying poverty, narrowly perceived and purged of its political content, become invisible and the social suffering it causes is also suppressed. Based on these claims, this article aims to re-examine the connection between the changing meaning of poverty and modern distributive justice and to support the argument that poverty must be expressed as a social relationship involving recognitional aspects rather than a simple expression of having a limited share of social goods.
Keywords: Poverty; Distributive Justice; Social Justice; Utilitarianism; Market; Capitalism; Recognition